Effective change of kindergarten students. (Journal of the College of Basic Education, 2022)
The current research aims to identify the effective change among the students of the kindergarten department, and the significance of the differences in the effective change among the students of the kindergarten department according to the variable of the academic stage. In order to achieve the objectives of the research, the two researchers built the effective change scale and then analyzed the scale’s paragraphs logically and statistically to calculate its discriminatory ability and its validity coefficients (the apparent honesty and the construction honesty). The stability coefficient of the effective change scale, it reached (0,889) by the re-test method, and by the Alpha-Cronbach method it reached (0,870). The scale of the effective change in its final form may consist of (45) items, And it was applied to the research sample of (410) female students from the Kindergarten Department at the College of Basic Education / Al-Mustansiriya University for the academic year (2021-2022), in a random way. and the research reached the following results:1- The kindergarten students enjoy effective change.2- There are statistically significant differences in the effective change of kindergarten students in the College of Basic Education / Al-Mustansiriya University according to the academic stage, and that the second stage students have a higher level than the first, third and fourth stage students in effective change.